Wet High-Intensity Magnetic Separation Of Industrial Minerals - W. E. Horst; W. P. Dyrenforth (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1971)
Although, separating or concentrating minerals, based on differences in. their magnetic properties has been practiced for years1 the early industrial applications of magnetic separators were involved with the most highly magnetic materials. These early separators were used to concentrate magnetite, separate metallic iron from furnace products, and separate iron and brass turnings. Next, the addition of a pretreatment operation, such as roasting or calcining, to transform certain iron-bearing minerals into a highly magnetic compound that could readily be separated from the altered mineral mixture using existing magnetic separation machines was added to the flowscheme. As the number of magnetic-separator installations grew, steady development of better equipment evolved including the design and implementation of induced magnets having high-intensity fields, These developments of course greatly expanded the field of magnetic separation and made it possible to commercially separate or concentrate very weakly magnetic minerals which previously had been considered as nonmagnetic minerals. A number of different designs of magnetic separators were well developed and the unit operation of magnetic separation was gaining wide acceptance in mineral processing operations when two events occurred that dampened these developments. First, the Mesabi iron range with its direct-shipping iron ore was discovered and placed into operation. This of course significantly reduced the need for magnetic separation to meet the raw material requirements of the iron and steel industry. Second, the advent of selective froth flotation, was so successful in solving many mineral process problems that electrical concentration techniques being developed at that time, including magnetic-separation methods, were either terminated or received low priority ratings. During the past two decades interest has been renewed in the use of electrical concentration methods to solve mineral separation problems. As the direct-shipping iron ore reserves are depleted more emphasis has been placed on magnetic upgrading of lower value iron ore available throughout the world. In addition, magnetic separation techniques have found numerous applications in the non-metallic and industrial minerals industry to supplement froth flotation and thus add to the variety of beneficiation methods available.